EU's and Japan's strategies for energy transition enhancement in Central Asia: Exploring comparative and synergic perspectives - Elena Shadrina (Energy Strategy Reviews)
In their pursuit of energy transitions, Central Asian emerging economies face limitations in technology and financing, which they address through international cooperation. Research about the engagement of the European Union (EU) and Japan, both relatively new non-regional actors in the Central Asian landscape, in renewable energy (RE) development in the region is limited. The contribution of this study is threefold: it (1) introduces a concept of Strategy for Energy Transition Enhancement (SETE) and operationalises it to (2) comparatively analyse the EU’s and Japan’s SETEs, and (3) explore avenues for cooperation to facilitate energy transitions in Central Asia. SETE is a multifaceted framework built upon the (Supra)National Energy Transition Strategy (NETS), elaborated through the channels of Energy Transition Diplomacy (ETD) and configured to fit global, regional, and host country contexts. The study demonstrates that SETE is driven by a pursuit of energy security and enabled by competitive advantages crucial for energy transition. It shows that despite the distinct approaches of the EU and Japan, driven by their respective energy security needs, technological priorities, institutional preferences, and growing global normative ambitions, both declare a greater interest in engaging in energy transition in Central Asia. The study uncovers an increasing synergy between the EU’s and Japan’s SETEs in Central Asia, which may help foster energy transition in the region.